Influencer marketing : how message value and credibility affect consumer trust of branded content on social media - Lou, Chen (2020)
In the past few years, expenditure on influencer marketing has grown exponentially. The present study involves preliminary research to understand the mechanism by which influencer marketing affects consumers via social media. It proposes an integrated model—the social media influencer value model—to account for the roles of advertising value and source credibility. To test this model, we administered an online survey among social media users who followed at least one influencer. Partial least squares (PLS) path modeling results show that the informative value of influencer-generated content, influencer’s trustworthiness, attractiveness, and similarity to the followers positively affect followers’ trust in influencers’ branded posts, which subsequently influence brand awareness and purchase intentions. Theoretical and practical implications are discussed.